Spectrum of clinical applications of interlead ECG heterogeneity assessment: From myocardial ischemia detection to sudden cardiac death risk stratification - Richard L. Verrier (Wiley, 2021)
Abstract Heterogeneity in depolarization and repolarization among regions of cardiac cells has long been recognized as a major factor in cardiac arrhythmogenesis. This fundamental principle has motivated development of noninvasive techniques for quantification of heterogeneity using the surface electrocardiogram (ECG). The initial approaches focused on interval analysis such as interlead QT dispersion and Tpeak–Tend difference. However, because of inherent difficulties in measuring the termination point of the T wave and commonly encountered irregularities in the apex of the T wave, additional techniques have been pursued. The newer methods incorporate assessment of the entire morphology of the T wave and in some cases of the R wave as well. This goal has been accomplished using a number of promising vectorial approaches with the resting 12‐lead ECG. An important limitation of vectorcardiographic analyses is that they require exquisite stability of the recordings and are not inherently suitable for use in exercise tolerance testing (ETT) and/or ambulatory ECG monitoring for provocative stress testing or evaluation of the influence of daily activities on cardiac electrical instability. The objectives of the present review are to describe a technique that has been under clinical evaluation for nearly a decade, termed “interlead ECG heterogeneity.” Preclinical testing data will be briefly reviewed. We will discuss the main clinical findings with regard to sudden cardiac death risk stratification, heart failure evaluation, and myocardial ischemia detection using standard recording platforms including resting 12‐lead ECG, ambulatory ECG monitoring, ETT, and pharmacologic stress testing in conjunction with single‐photon emission computed tomography myocardial perfusion imaging.